Meningitis and epididymitis caused by Toscana virus infection imported to Switzerland diagnosed by metagenomic sequencing: a case report - Tschumi, Fabian; Schmutz, Stefan; Kufner, Verena; Heider, Maike; Pigny, Fiona; Schreiner, Bettina; Capaul, Riccarda; Achermann, Yvonne; Huber, Michael (BMC infectious diseases, 2019)
Background We report a rare case of Toscana virus infection imported into Switzerland in a 23-year old man who travelled to Imperia (Italy) 10 days before onset of symptoms. Symptoms included both meningitis and as well epididymitis. This is only the fourth case of Toscana virus reported in Switzerland. Case presentation The patient presented with lymphocytic meningitis and scrotal pain due to epididymitis. Meningitis was initially treated with ceftriaxone. Herpes simplex, tick-borne encephalitis, enterovirus, measles, mumps, rubella and Treponema pallidum were excluded with specific polymerase chain reaction (PCR) or serology. In support of routine diagnostic PCR and serology assays, unbiased viral metagenomic sequencing was performed of cerebrospinal fluid and serum. Toscana virus infection was identified in cerebrospinal fluid and the full coding sequence could be obtained. Specific PCR in cerebrospinal fluid and blood and serology with Immunoglobulin (Ig) M and IgG against Toscana virus confirmed our diagnosis. Neurological symptoms recovered spontaneously after 5 days. Conclusions This case of Toscana virus infection highlights the benefits of unbiased metagenomic sequencing to support routine diagnostics in rare or unexpected viral infections. With increasing travel histories of patients, physicians should be aware of imported Toscana virus as the agent for viral meningitis and meningoencephalitis.